MAQÄá¹¢ID AL-SYARÄªâAH AL-SYÄá¹¬IBÄª DAN AKTUALISASINYA DALAM NILAI-NILAI FALSAFAH PANCASILA - Ahmad, Agustan (Institut Agama Islam Negeri (IAIN) Palu, 2011)
Abstract: Allah swt. lowering of the Sharia to mankind is not without purpose. Sharia is the revelation of the purpose to provide the benefit to mankind and prevent them from things that are not good. However, the understanding sharia scholars about the purpose and application procedures are not always the same. Therefore, the problem maqasid al-Sharia become the object of a separate study in Islamic law. One scholar who specifically addresses this issue is As-Syatibi in his book al-MuwafaqÄt. Sharia is not the same as the Pancasila as the latter is nothing more than the ideas of the freedom fighters of Indonesia, yet it contains the philosophy to the benefit of the people of Indonesia in this context, the principal study in this paper focus on the actualization Maqasid al-Sharia in the philosophy of Pancasila values.Kata Kunci: maqasid al-syariah, syariat, al-saytibi, falsafah Pancasila